The Poseidon adventure [videorecording (DVD)] - Neame, Ronald; Hackman, Gene; Borgnine, Ernest, 1917-2012; Buttons, Red, 1919-2006; Winters, Shelley; Gallico, Paul, 1897-1976 (20th Century Fox, 2006)
A group of passengers struggle to survive and escape when their ocean liner completely capsizes at sea. Bonus features include: lobby cards, commentary, behind-the-scenes featurettes, and more!